Dual-color fluorescence lifetime correlation spectroscopy to quantify protein-protein interactions in live cell. - Padilla-Parra, S; Audugé, N; Coppey-Moisan, M; Tramier, M (2011)
Dual-color fluorescence correlation spectroscopy is an interesting method to quantify protein interaction in living cells. But, when performing these experiments, one must compensate for a known spectral bleed through artifact that corrupts cross-correlation data. In this article, problems with crosstalk were overcome with an approach based on fluorescence lifetime correlation spectroscopy (FLCS). We show that FLCS applied to dual-color EGFP and mCherry cross-correlation allows the determination of protein-protein interactions in living cells without the need of spectral bleed through calibration. The methodology was validated by using EGFP-mCherry tandem in comparison with coexpressed EGFP and mCherry in live cell. The dual-color FLCS experimental procedure where the different laser intensities do not have to be controlled during experiment is really very helpful to study quantitatively protein interactions in live sample.